Implementation of Outing Class Learning as a Means of Developing Social Interaction Skills for Autistic Students - Emy Purwanti; Wiwik Widajati; Budiyanto Budiyanto (Jurnal ORTOPEDAGOGIA, 2025)
People with Autism or Autistic Spectrum Disorder (ASD) are someone who has a developmental disorder that affects several aspects such as speech, communication, social interaction, sensory, behavior and emotions when learning from experiences with the surrounding environment. Autistic children tend to behave differently from people in general, seem to not care about the environment around them and prefer to be alone as if they live in their own world. The aim of this research is to obtain data that provides an overview of how outing class activities are implemented as a means of improving social interaction skills in autistic students. This research design uses descriptive research with a qualitative approach. In the data collection process, the instruments chosen by researchers were interviews, observation and documentation. Data analysis researchers used the data analysis technique of the Miles and Huberman model in Sugiyono (2017) which consists of 3 stages, namely data reduction, data presentation, and drawing conclusions. The research results show that the description of the implementation of outing class learning starts from preparation to follow-up. Preparation consists of preparing tools and materials as well as planning the implementation of learning. Meanwhile, the implementation is carried out in accordance with the learning implementation plans that have been implemented previously. The follow-up to the outing class learning is an evaluation of the implementation of the learning to improve further learning objectives.